Human impact on river planform within the context of multi-timescale river channel dynamics in a Himalayan river system - Vercruysse, Kim; Grabowski, Robert C. (Elsevier, 2021)
Rivers are dynamic landscape features which are often altered by human activity, making it difficult to disentangle human impact on geomorphic change from natural river dynamics. This study evaluated the human impact on river planform change within the context of short- and long-term river channel dynamics in the Himalayan Sutlej and Beas Rivers, by (i) systematically assessing river planform change over centennial, annual, seasonal and episodic timescales; (ii) connecting observed changes to human-environment drivers; and (iii) conceptualising these geomorphic changes in terms of timescale-dependent evolutionary trajectories (press, ramp, pulse). Landsat imagery was used to extract components of the post-monsoon active river channel (1989-2018), using the modified Normalized Differences Water Index to identify the wet river area, and visible red to determine active gravel bars. Findings were compared with a historical map to represent the pre-dam period (1847-1850) and with data on potential driving factors of change (discharge, climate and land cover). River planform characteristics changed significantly over all timescales, exhibiting strong spatiotemporal variation between and within both rivers. Dam construction likely caused channel narrowing and straightening at the centennial scale (press trajectory). In the Sutlej, this process has continued over the last 30 years, likely enforced by the cumulative effect of water abstraction and climatic changes (ramp trajectory). In the Beas, the pattern of change in river planform metrics was less pronounced over the same period and more variable along the length of the river, possibly linked to different dam operations that maintain a higher degree of flow variability and peak flows (press trajectory). High local erosion rates caused by aggregate mining (episodic) in the Sutlej were also observed (pulse trajectory). Expressed as evolutionary trajectories, the observed responses to human activity confirm the importance of legacy effects of human impact on river systems, and stress the dependency on spatial and temporal scales to determine trajectories of change. The multi-timescale assessment and conceptualisation provide insights into different dimensions of human impact on river planform change, which is pivotal to developing holistic management strategies
Keywords: evolutionary trajectories; timescale; hydro-electric dams; Fluvial geomorphology